THE ROLE OF DIMENSIONS OF JOB ENGAGEMENT IN ORGANIZATIONAL PERFORMANCE - Chukuakadibia ERESIA-EKE; Olippa NDLOVU; Taguma NYANGA (Prizren Social Science Journal, 2023)
Job engagement is about the degree of connection employees have with their work. Engagement theories suggest that employees experience engagement cognitively, emotionally, and physically. If and the extent to which this is the case, specifically within South African municipalities, remains largely indeterminate.